Application of SPM to Detect the Wind Turbine Bearing Fault - Ruifeng Yang; Jianshe Kang; Xinghui Zhang; Hongzhi Teng; Haiping Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the widespread application of wind turbines, the Maintenance issue gets growing concern. Bearings play a critical role in industrial applications. It is necessary to effectively monitor their health status. The shock pulse method (SPM) can detect the incipient fault of bearings and prevent the fault consequence effectively. However, many researchers used laboratory data to validate the SPM. This paper mainly concentrates on the SPM application on bearing fault detection of wind turbines. Shock pulse signals are derived from the gearbox of industrial wind turbine test rig by SPM instrument. According to frequency spectrum analysis, the bearing fault has been accurately detected and located. The analysis results demonstrate that the SPM technology is potentially effective for detecting the bearing faults of industrial wind turbines. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4122